Assessing Patient Participation in Health Policy Decision-Making in Cyprus - Kyriakos Souliotis; Eirini Agapidaki; Lily Evangelia Peppou; Chara Tzavara; George Samoutis; Mamas Theodorou (Kerman University of Medical Sciences, 2016)
Although the importance of patient participation in the design and evaluation of health programs and services is well-documented, there is scarcity of research with regard to patient association (PA) participation in health policy decision-making processes. To this end, the present study aimed to validate further a previously developed instrument as well as to investigate the degree of PA participation in health policy decision-making in Cyprus. A convenient sample of 114 patients-members of patients associations took part in the study. Participants were recruited from an umbrella organization, the Pancyprian Federation of Patient Associations and Friends (PFPA). PA participation in health policy decision-making was assessed with the Health Democracy Index (HDI), an original 8-item tool. To explore its psychometric properties, Cronbach α was computed as regards to its internal consistency, while its convergent validity was tested against a self-rated question enquiring about the degree of PA participation in health policy decision-making. The findings revealed that the HDI has good internal consistency and convergent validity. Furthermore, PAs were found to participate more in consultations in health-related organizations and the Ministry of Health (MoH) as well as in reforms or crucial decisions in health policy. Lower levels were documented with regard to participation in hospital boards, ethics committees in clinical trials and health technology assessment (HTA) procedures. Overall, PA participation levels were found to be lower than the mid-point of the scale. Targeted interventions aiming to facilitate patients' involvement in health policy decision-making processes and to increase its impact are greatly needed in Cyprus.